THE EFFECT OF STORYTELLING STRATEGY ON THE ABILITY OF FIRST YEAR STUDENTS OF SMAN 1 PEKANBARU IN READING COMPREHENSION - Ramadani, Rezki Mediana; ', Mahdum; ', Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed at finding out whether there is a significant effect of Storytelling strategy on the ability of first year students of SMAN 1 Pekanbaru in reading comprehension. The research design is a pre-experimental research with one group pre-test and post-test design. The sample was X MIA-2 chosen by using cluster random sampling technique. The result showed that the mean score of post-test (76.00) was higher than mean score of pre-test (70.03). The value of t-test (15.48) was higher than t-table (2.04) at 5% of the significance level and t-table (2.75) at 1% of the significance level. Therefore, Alternative Hypothesis (Ha) was accepted and Null Hypothesis (Ho) was rejected. It could be concluded that there was a significant effect of Storytelling strategy on the ability of first year students of SMAN 1 Pekanbaru in reading comprehension.Keywords: Storytelling, Reading Comprehension